Analisis fluktuasi harga ayam kampung di Provinsi Sulawesi Tenggara - La Ode Arfan Dedu; Hartina Batoa; Hadi Sudarmo; Hartatia Nur; Normal Bivariant Padangaran; Pertiwi Syarni; Rahayu Endah Purwanti (AGROINTEK, 2026)
Free-range chicken is widely cultivated in Indonesian society traditionally, and usually the demand will be very high on major religious holidays, especially Islam, both on Eid al-Fitr and Eid al-Adha. The purpose of this study was to determine the price fluctuations of native chicken in Southeast Sulawesi in 2022 and 2023 and to determine the price trend of native chicken in Southeast Sulawesi in 2022 and 2023. This research was conducted in Southeast Sulawesi Province. Determination of this location is determined intentionally ( purposive). The data source used in this study is secondary data (time series) for the last 2 years, namely from 2022 to 2023. Data collection procedures/techniques in this study are using literature studies. Data analysis uses change analysis and trend analysis. The results showed that the price of native chicken in Southeast Sulawesi Province during the last two years, namely 2022-2023, experienced increasing fluctuations and the trend of native chicken prices in Southeast Sulawesi Province during the last 2 years, namely 2022-2023, showed an increasing trend, where the average trend was positive.